MENGKAJI POLITIK HUKUM KEBEBASAN BERAGAMA DAN BERKEYAKINAN DI INDONESIA - Muktiono Muktiono (Jurnal Dinamika Hukum, 2012)
Indonesia has entered the era of human rights characterized by increasingly massive domestication of the international human rights norms in national legal system. In such a situation, in fact, the rights to freedom of religion and of belief for minorities have not received their benefits and instead they become victims. This Article seeks to investigate how it can happen by using the legal politics analysis as perspective. Legal politics here will focus on how the governments of several regimes in Indonesia have used their legislation and policy to regulate matters relating to the rights to freedom of religion and belief. In addition, it will also see how the Constitutional Court contributed to this issue by influencing the legal politics as this Court is the sole authority in interpreting the constitutional right to the freedom of religion and belief thereby affecting its normation and implementation. Key words:  Religious minority group, human rights, legal politics of Indonesia